2022
DOI: 10.3390/photonics9090642
|View full text |Cite
|
Sign up to set email alerts
|

Single Image Deblurring for Pulsed Laser Range-Gated Imaging System with Multi-Slice Integration

Abstract: The multi-slice integration (MSI) method is one of the approachs to extend the depth of view (DOV) of the pulsed laser range-gated imaging (PLRGI) system. When the DOV is large enough and exceeds the depth of focus of the system, it may make some targets in the image clear and others blurred. In addition, forward scatter is also considered to have a blurring effect on the image. There is very little literature to solve the combined effect of forward scatter and defocus. An imaging model is built based on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that different levels of blur in images can be better handled from multi-scale images [28]. Lin et al [29] used a transformer-based deep learning model for image deblurring and used the imaging model to generate 16 different blurring kernels to adapt the model to different degrees of blurred images, and the results show that the proposed method can remove different degrees of blurring and can handle images with both clear and blurred targets. Based on this, various CNN-based deblurring methods have also adopted this idea where blurred images of different scales are used as inputs to each sub-network [30], and a coarse-to-fine design principle has proven to be effective for image deblurring.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that different levels of blur in images can be better handled from multi-scale images [28]. Lin et al [29] used a transformer-based deep learning model for image deblurring and used the imaging model to generate 16 different blurring kernels to adapt the model to different degrees of blurred images, and the results show that the proposed method can remove different degrees of blurring and can handle images with both clear and blurred targets. Based on this, various CNN-based deblurring methods have also adopted this idea where blurred images of different scales are used as inputs to each sub-network [30], and a coarse-to-fine design principle has proven to be effective for image deblurring.…”
Section: Introductionmentioning
confidence: 99%